Improving guideline-mandated care of patients with implantable cardiac defibrillators. (2nd August 2020) - Garner, Daniel; Blackburn, Matthew; Wright, David J; Rao, Archana
Abstract : Background/Aims: Implantable cardiac defibrillators reduce the risk of sudden cardiac death in selected patients. The value of an implantable cardiac defibrillator declines as the patient's disease progresses. Guidelines suggest that the appropriateness of maintaining implantable cardiac defibrillator therapy be regularly reviewed as part of monitoring of the patient's disease trajectory. It is recommended that implantable cardiac defibrillators are deactivated as patients approach the end of life. Patients with a better understanding of their current state of health and the role that the implantable cardiac defibrillator plays within it are more likely to make informed decisions about the timing of deactivation. Methods: A quality improvement project was undertaken on appropriate deactivation of implantable cardiac defibrillators within a large tertiary cardiac centre. This was driven by audit data showing inadequate patient communication and documentation around deactivation. Drivers for change included the introduction of electronic data records, clinical review of comorbid patients approaching elective battery change and an ongoing forum for patient and carer education. Measured outcomes included the number of deactivations performed, evidence of patient discussion and consent, and timing of deactivation of the implantable cardiac defibrillator. Results: There were increased numbers of timely device deactivations undertaken following the interventions with improved documented evidence of patient discussion and consent. The educational forum was received favourably. Conclusions: Focused multidisciplinary interventions can impact favourably on appropriate implantable cardiac defibrillator deactivation and improve patient engagement.